Fire salamander (Salamandra salamandra) in Larzac plateau: low occurrence, pond-breeding and cohabitation of larvae with paedomorphic palmate newts (Lissotriton helveticus) - Mathieu Denoël; Laurane Winandy (Acta Herpetologica, 2014)
Alternative reproductive strategies are widespread in caudate amphibians. Among them, fire salamanders (Salamandra salamandra) usually rely on streams to give birth to aquatic larvae but also use ponds, whereas palmate newt larvae (Lissotriton helveticus) typically metamorphose into terrestrial juveniles, but can also reproduce in retaining their gills, a process known as paedomorphosis. Here we report repeated observations of an unusual case of coexistence of these two alternative traits in the same pond (Larzac, France). The prevalence of fire salamanders in Southern Larzac was very low (pond occupancy: 0.36%). The observed abundance of fire salamander larvae and paedomorphic newts was also low in the studied pond. On one hand, the rarity of this coexistence pattern may suggest that habitat characteristics may not be optimal or that competition or predation processes might be operating. However, these hypotheses remain to be tested. On the other hand, as this is the only known case of breeding in Southern Larzac, it could be considered to be at a high risk of extirpation.